Determinants of Investment Behavior in Mutual Funds: Evidence From Pakistan - Saleem, Sharaz; Mahmood, Faiq; Usman, Muhammad; Bashir, Mohsin; Shabbir, Rizwan (Frontiers in Psychology, 2021)
This paper aims to provide empirical evidence on the investor's behavior towards mutual funds by considering the relationship of it with Risk Perception, Return Perception, Investment Criteria, Mutual Fund Awareness, and Financial Literacy for Mutual Fund investors. By using a Questionnaire, the data has been collected from 500 Mutual Fund investors from which 460 questionnaires are used for the analysis. Snowball Sampling Technique has been used to collect data from different cities of Pakistan. This study shows that Risk Perception, Return Perception (RP), and Mutual Fund Awareness (MFA) have been Negative and Insignificant effects on Mutual Fund Investors' behavior. Investment Criteria has Negative but Significant on Mutual Fund Investors Behavior. Financial Literacy has a positive and insignificant effect on Mutual Fund Investors Behavior. The study was limited to 460 investors. The research has been conducted to analyze only some factors affecting the Investment Behavior of investors. In this research sample, Female existence is very-low. This research enforced the technique of snowball sampling and may not be representative of the actual population. The results could also provide better information and guidance for investors as well as policy-makers on the factors that affect the Mutual Fund Investors' behavior.